Recent advances in amphiphilic polymers for simultaneous delivery of hydrophobic and hydrophilic drugs. (January 2016) - Martin, Chloe; Aibani, Noorjahan; Callan, John F; Callan, Bridgeen
Nanomedicine has evolved with the use of biological compounds such as proteins, peptides and DNA. These hydrophilic and often highly charged compounds require a delivery system to allow effective transport and release at the site of action. These new biological therapeutics have not replaced the more traditional smaller molecule, but instead are working synergistically to the benefit of the end user. To that end, drug delivery systems are now required to encapsulate both larger hydrophilic compounds as well as the smaller and generally more hydrophobic compound. This review highlights the emerging role in drug delivery of amphiphilic polymers that by their very nature can associate with compounds of differing physicochemical properties, in particular the role of micelles, polymersomes and nanocapsules.